PERLINDUNGAN HUKUM BAGI KORBAN PENCURIAN INFORMASI PRIBADI MELALUI DUNIA CYBER DITINJAU DARI UNDANG-UNDANG NO. 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK (UU ITE) - Wahyu Putra, R. Caesalino; Parikesit Widiatedja, I Gusti Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2015)
The negative impact of technological development can be seen from the occurrence of the phenomenon in the world of cyber crime that commonly referred as cyber crime, such as to steal of personal information in the form of personal data, ATM data and credit card data, from the Background author lifted a journal Entitled "Legal Protection for Theft of Personal Information Victims Through World Cyber review from Act No. 11 of 2008 on Information and Electronic Transactions (UU ITE). This paper using normative methods by assessing the vacuum of law regarding the protection of the victim on the perspective of the ITE Act.. The purpose of this paper is to identify the forms of legal protection that can be given to the victim. Restitution is a form of legal protection for victims of cyber crime, in the form of material compensation granted by the perpetrator.
Keywords: Legal Protection, Criminal Act of Theft, Cyber Crimes, Restitution